Hypo-osmotic swelling test identifies individual spermatozoa with minimal DNA fragmentation - Stanger, J.; Vo, Long; Yovich, J.; Almahbobi, Ghanim (Elsevier, 2010)
One concern during intracytoplasmic sperm injection (ICSI) is that selected spermatozoa may have increased levels of DNA damage; however, the available testing for this is largely destructive in nature and therefore unsuitable as a tool for sperm selection. One alternative selection process that has previously achieved pregnancies is the hypo-osmotic swelling test (HOST). This study reports that low HOST values of neat semen samples were significantly (P < 0.001) associated with increased DNA damage identified by the DNA fragmentation index (DFI) from the sperm chromatin structure assay as well as the TdT-mediated dUTP nick-end labelling (TUNEL) assay. The HOST value was highly predictive of an abnormal DFI value by receiver operating characteristic curve analysis (P < 0.001). Furthermore, when individual spermatozoa were assessed for both HOST status and DNA fragmentation by TUNEL, the key HOST-induced tail-swelling grades D, E and F were most commonly associated with high HOST values and were significantly (P < 0.001) associated with minimal DNA damage regardless of the DNA status of the ejaculate. The application of HOST may be a valuable tool in the routine identification and selection of viable, DNA-intact individual spermatozoa for ICSI after further research to demonstrate its efficacy and safety.The hypo-osmotic resistance by spermatozoa, as measured by the hypo-osmotic swelling test, was shown to strongly predict the degree of sperm DNA damage when assessed by the sperm chromatin structure assay. The spermatozoa that displayed only distal swelling were shown to strongly correlate to spermatozoa with minimal DNA damage. This study suggests that such spermatozoa may be suitable candidates for selection of viable spermatozoa for microinjection in intracytoplasmic sperm injection cycles.